1980
DOI: 10.1017/s000335610002417x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of type of silage and level of concentrate supplementation offered during early lactation on total lactation performance of January/February calving cows

Abstract: A 3 × 2 factorial design experiment using 84 British Friesian cows was conducted to assess the effect of offering three types of grass silage and two levels of concentrate supplementation during early lactation on the total lactation performance of cows which calve during January and February. The three types of silage were early-cut wilted (ECW), early-cut unwilted (ECU) and late-cut unwilted (LCU), and the two levels of concentrate supplementation were 538 kg (LC) and 738 kg (HC) during a mean post-calving p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
8
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 11 publications
7
8
0
Order By: Relevance
“…The precision-wilted silage had a higher pH than the flial-direct silage, an effect which is usually obtained following wilting (Derbyshire et al, 1976;Steen and Gordon, 1980;Castle and Watson, 1982) and was also reported by Parker (1982) in a similar comparison to that reported here. Degree of chopping at harvest has generally not influenced silage pH when an effective additive has been applied (Gordon, 1982;Gordon and Unsworth, 1985) although Murphy (1983) has noted higher pH values when very long silages, produced by forage wagons, were compared with short chop material harvested via precision-chop harvester.…”
Section: Effect Of Harvesting Systemsupporting
confidence: 91%
“…The precision-wilted silage had a higher pH than the flial-direct silage, an effect which is usually obtained following wilting (Derbyshire et al, 1976;Steen and Gordon, 1980;Castle and Watson, 1982) and was also reported by Parker (1982) in a similar comparison to that reported here. Degree of chopping at harvest has generally not influenced silage pH when an effective additive has been applied (Gordon, 1982;Gordon and Unsworth, 1985) although Murphy (1983) has noted higher pH values when very long silages, produced by forage wagons, were compared with short chop material harvested via precision-chop harvester.…”
Section: Effect Of Harvesting Systemsupporting
confidence: 91%
“…This small reduction in milk yield following wilting is directly in line with that reported in other studies from this Institute (Gordon, 1980a;Steen and Gordon, 1980;Gordon, 1981) and has also been obtained elsewhere Watson, 1982 and. This small reduction in milk yield following wilting is directly in line with that reported in other studies from this Institute (Gordon, 1980a;Steen and Gordon, 1980;Gordon, 1981) and has also been obtained elsewhere Watson, 1982 and.…”
Section: Effect Of Wilting Of Grass For Silagesupporting
confidence: 90%
“…The precision-wilted silage had a higher pH, in line with the high degree of wilting used in the present study (Steen and Gordon, 1980;Derbyshire et al., 1976;Gordon, 1981), reflecting the lower level of acid production recorded and similar to that reported by McDonald et al, (1968). However, there were also higher ammonia and butyric acid contents with the precisionwilted silage suggesting that while fermentations in both silages were good the flail-direct silage was more stable than the precision-wilted.…”
Section: Effect Of Harvesting Systemsupporting
confidence: 87%